2022
DOI: 10.3390/math11010104
|View full text |Cite
|
Sign up to set email alerts
|

Three-Echelon Supply Chain Management with Deteriorated Products under the Effect of Inflation

Abstract: A business can be properly managed globally when it is under a supply chain. When it is a global supply chain, inflation has a huge effect on supply chain profit. Another important factor is the deterioration of products. Products can deteriorate during storage or transportation, which badly affects each supply chain player. This study develops a three-echelon supply chain model through which products can be delivered to customers easily. In this model, one producer and multiple buyers are considered, and each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In light of the effects of price variations on overall profit, recent researches have proposed novel models to manage supply chains with uncertain demand and inflation. Businesses can benefit from extra advice from the three-level supply chain model by Padiyar et al [13] and the Stackelberg game-based model by Mahdavisharif et al [14] to increase their inventory management and general profitability. The literature review provided corresponds to the data presented in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In light of the effects of price variations on overall profit, recent researches have proposed novel models to manage supply chains with uncertain demand and inflation. Businesses can benefit from extra advice from the three-level supply chain model by Padiyar et al [13] and the Stackelberg game-based model by Mahdavisharif et al [14] to increase their inventory management and general profitability. The literature review provided corresponds to the data presented in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inflation, a general increase in prices and fall in the purchasing value of money, can have significant implications on the supply chain (Padiyar et al, 2022 ). One of the primary impacts is the potential for shrinking demand.…”
Section: Inflationmentioning
confidence: 99%
“…Another significant impact of inflation on the supply chain is the increase in costs. Inflation can drive up the direct costs for materials, labor, energy, and transportation (Padiyar et al, 2022;Furceri et al, 2022). As a result, it becomes more expensive to manufacture, store, and ship goods.…”
Section: Inflationmentioning
confidence: 99%
“…On this basis, Xiang and Xu [15] considered the impact of big data marketing, technological innovation, and overconfidence on the closed-loop remanufacturing supply chain and found that an appropriate cost-sharing ratio can be a "win-win" for both the manufacturers and third-party Internet recycling platforms, but excessive confidence levels can dampen the incentives for cost-sharing strategies and negatively affect the interests of the manufacturers. Singh et al [16] investigated the impact of inflation on supply chain profits by constructing a three-level supply chain model and found a negative correlation between the supply chain profits and the rate of inflation.…”
Section: Optimal Decision-making For Closed-loop Supply Chainsmentioning
confidence: 99%